Bedside Catheter Hematoma Evacuation in Vitamin K Antagonist-Related Intracerebral Hemorrhage: A Safe and Feasible Approach - Volbers, Bastian; Niesen, Wolf-Dirk; Amiri-Soltani, Samuel; Staykov, Dimitre; Shah, Mukesch Johannes; Lang, Stefan; Lücking, Hannes; Kuramatsu, Joji B.; Huttner, Hagen B.; Schwab, Stefan; Bardutzky, Jürgen (Frontiers in Neurology, 2020)
Background and Purpose: Although outcome in intracerebral hemorrhage (ICH) patients is generally not improved by surgical intervention, the use of minimally invasive surgery (MIS) has shown promising results. However, vitamin K antagonist (VKA)-related ICH patients are under-represented in surgical treatment trials. We therefore assessed the safety and efficacy of a bedside MIS approach in VKA-related ICH. Methods: Patients with a VKA-related ICH > 20 ml who received bedside hematoma evacuation treatment (n=21) at the University Medical Center Freiburg were retrospectively included for analysis and compared to a historical control group (n=35) selected from an institutional database (University Medical Center Erlangen) according to identical inclusion criteria. Propensity score matching was performed to obtain comparable cohorts. The evolution of hematoma and peri-hemorrhagic edema (PHE) volumes, midline shift, and the occurrence of adverse events were analyzed. Furthermore, we assessed the modified Rankin Scale and NIHSS scores recorded at discharge. Results: Propensity score matching resulted in 16 patients per group with well-balanced characteristics. Median ICH volume at admission was 45.7 (IQR: 24.2–56.7) ml in the control group, and 48.4 (IQR: 28.7–59.6) ml in the treatment group (p=0.327). ICH volume at day 7 was less pronounced in the treatment group (MIS: 23.2 ml [IQR: 15.8–32.3] vs. control: 43.2 ml [IQR 27.5–52.4]; p=0.013), as was the increase in midline shift up to day 7 (MIS: -3.75 mM [IQR: -4.25 to -2) vs. control: 1 mM [IQR: 0-2]; p<0.001). No group differences were observed in PHE volume on day 7 (MIS: 42.4 ml [IQR: 25.0–72.3] vs. control: 31.0 ml [IQR: 18.8–53.8]; p=0.274) or mRS at discharge (MIS: 5 [IQR: 4–5] and 5 [IQR: 4–5]; p=0.949). No hematoma expansion was observed. The catheter had to be replaced in 1 patient (6%). Conclusions: Bedside catheter-based hematoma evacuation appears to be feasible and safe in cases of large VKA-related ICH. Further studies that assess the functional outcome associated with this technique are warranted. Clinical Trial Registration: DRKS00007908 (German Clinical Trial Register; www.drks.de)